Financial Literacy of the Banking Sector in Micro and Small Business in Semarang - ., Karsinah; Rahayu Kistanti, Nurjannah; Ineke Putri, Phany (KnE Social Sciences, 2020)
The purposes of this research are to analyze the characteristics and financial literacy of MSMEs in Semarang. The data used are primary data and secondary data. The method used in this study is descriptive quantitative. The sample in this study were small micro-businesses and small businesses in the city of Semarang. The level of financial literacy in Semarang by giving questions as many as 28 questions taken and modified from Chen and Volpe. The results showed that 79% of MSMEs literacy in Semarang was in the medium category, 18% low and 3% high. If viewed further on the financial literacy of MSMEs, it is divided into 4 aspects, they are personal finance knowledge, savings and debts, Investments and insurance aspects. The average MSMEs for general knowledge of personal finance in the medium category was 76.60%, the savings and debts dimension medium category 81.91%, the investment aspect was the medium category 45.74% and the low category 59.57% of MSMEs financial literacy for insurance. This shows that the financial literacy level of SMEs in Semarang still needs to be improved in order to be able to compete and improve business. Keywords: literacy, financial, banking, micro and small business